Consumo de drogas en adolescentes. Una reflexión conceptual (2019)
The reflection article addresses in a conceptual dimension the issue of drugs, consequences, intervention and proposed analysis. It generates four argumentative sec-tions, which are discriminated against in this way: The first section explains drugs and prevalence, referring to the 60% increase in the number of consumers in South America and the existence of 63% of students in Colom-bia who mention having consumed a drug. The second describes the action of drugs in the dopaminergic system and their affectation in the central nervous system, in addition to other affectations emphasizing state policies to address the problem situation. The third body of the ar-ticle explains the demand through two models, one shows consumption, functioning and neurological consequences and the other seeks to understand the antecedents of the decision and action of consumption, with coherent results, but not conclusive. Based on the above, the choice and con-sumption of drugs is explained through the integration of a cognitive thesis such as intentionality, explained by the theory of planned behavior and the neuropsychological thesis with executive functions associated with decision making, planning and inhibition. The fourth section refers to the vulnerability in adolescence to make choices and plan short-term goals with future disadvantage and raises the possibility that negative intention and high maturity in Executive Functions (FE) would lead to in-hibition of choice and consumption as opposed to positive intention and low maturity of FE that would lead to posi-tive trend choices and consumption.